2016
DOI: 10.1136/bmjsem-2015-000089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiovascular risk-lowering health benefits accruing from laboratory-based, community-based and exercise-referral exercise programmes

Abstract: BackgroundTo evaluate the ability of community-based exercise programmes to facilitate public participation in exercise and hence improved cardiovascular health, we assessed the respective impacts of: a continuously monitored exercise programme based within our university (study 1); a Valleys Regional Park-facilitated community-based outdoor exercise programme (study 2); a Wales National Exercise Referral Scheme-delivered exercise-referral programme (study 3).MethodsBiomolecular (monocytic PPARγ target gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…The mean baseline SBP for participants in the database was 131.70±16.91 mmHg; thus, considering the results of Bundy et al 47 highlighting that large SBP reductions produce the greatest mortality risk reduction, in combination with the small reduction reported here, it is unclear whether sufficient reduction might have occurred to have meaningfully reduced risk. Though other studies of ERSs also report reductions in SBP, these are either similarly small (−2.84 mmHg (−6.57 to 0.82) and −3.53 mmHg (−7.31 to 0.25)22; −3.2 mmHg (−4.6 to 1.7) and −2.9 mmHg (−4.4 to 1.4)38) or variable in their point estimates (−6.1 to +4.8 mmHg40). This is perhaps unsurprising as meta-analysis48 suggests reductions are small for endurance type exercise (−3.5 mmHg (−4.6 to −2.3) and dynamic resistance training (−1.8 mmHg (−3.7 to −0.011)).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The mean baseline SBP for participants in the database was 131.70±16.91 mmHg; thus, considering the results of Bundy et al 47 highlighting that large SBP reductions produce the greatest mortality risk reduction, in combination with the small reduction reported here, it is unclear whether sufficient reduction might have occurred to have meaningfully reduced risk. Though other studies of ERSs also report reductions in SBP, these are either similarly small (−2.84 mmHg (−6.57 to 0.82) and −3.53 mmHg (−7.31 to 0.25)22; −3.2 mmHg (−4.6 to 1.7) and −2.9 mmHg (−4.4 to 1.4)38) or variable in their point estimates (−6.1 to +4.8 mmHg40). This is perhaps unsurprising as meta-analysis48 suggests reductions are small for endurance type exercise (−3.5 mmHg (−4.6 to −2.3) and dynamic resistance training (−1.8 mmHg (−3.7 to −0.011)).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, in their systematic review and meta-analysis, Pavey et al 18 reported no significant (or meaningful considering the criteria used here) differences for the effects of ERSs compared with other comparator interventions on BMI. Studies of ERS ranging from 8 weeks to 4 months show similarly little changes in BMI (ie, ranging from no change to ~0.6 kg/m 2 22 38–40). Considering that participants undergoing ERSs in our sample were obese (BMI 31.53±6.53 kg/m 2 ), lack of effectiveness could be considered an issue, particularly as ERSs have been noted as being tied to the current ‘obesity agenda’ 41.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, it may be that if longer schemes where present in the database for analysis these may reveal greater physical activity increases compared with shorter schemes. Although other research by Webb, et al (2016) suggests shorter schemes can be effective as it was found that after completing an 8-week ERS, categorical IPAQ scores significantly increased.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, ERSs have been described as 'wild and woolly', with a lack of agreement between stakeholders on how to determine impact (Henderson, et al 2018). Although increasing physical activity levels is a primary aim of ERS there has been little research documenting change in physical activity levels after scheme completion; and what has been conducted appears conflicting (Chalder, et al 2012;Murphy, et al 2012;Pavey, et al 2011;Webb, et al 2016). This is of particular relevance as recent observational findings reported alongside this manuscript from ERSs schemes in The National Referral Database suggest that changes in health and wellbeing outcomes may not reach meaningful levels (Wade et al 2019).…”
Section: Introductionmentioning
confidence: 99%